The positive side of artificial intelligence as a key tool for language expertise ​​(The Spanish as a model) - Enas Sadiq Hamudi , Ass.Prof (lark, 2025)
Artificial intelligence (AI) has experienced strong growth in recent decades, becoming a transformative tool that can revolutionize various aspects of human life. In recent years it has demonstrated the ability to solve complex problems, from medical assistance to the proposal of self-sufficient objects that manage to effectively carry out human activities.Now, this transformative power of AI has arrived on the education stage, offering innovative and personalized solutions for teachers and students. In the case of teachers, it can become a virtual assistant that facilitates the planning and evaluation exercise, while, for students, it provides varied exercise spaces. The latter is very valuable for the Spanish class in Iraq, since personalized support helps advance mastery of the language.For the reasons stated, this article proposes to show how AI can become a tool for learning Spanish in the ELE class in Iraq. In that order, the first thing is to cover its conceptualization, its benefits and the role it can have in language learning. As well as, the challenges involved in understanding its use and adaptation, the different strategies to promote and the specific tools for the Spanish class in the Iraqi context.
Keywords: Artificial Intelligence